CGIAR report concerning Centers' implementation of their Article 15 Agreements: for the 9th Session of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture - Halewood, Michael; Lopez Noriega, Isabel (2022)
This CGIAR report concerning centers' implementation of their Article 15 agreements was presented to the 9th session of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty), in 2022